Factor Analysis in Understanding The Spread of Sexually Transmitted Diseases in West Java Province - Citra, Leysha Adinda; Adelard, Muhammad Daffa; Rahmawati, Rizqa; Illahi, Mohammad Raihan Anugrah; Handawati, Rayuna (Jurnal Penelitian Geografi (JPG), 2024)
This study aims to analyze the factors that contribute to the spread of sexually transmitted diseases (STDs) in West Java Province, using a Final Project Based Learning approach. The study uses a mixed-methods research design, combining quantitative and qualitative data collection and analysis methods. The results show that the prevalence of STDs in West Java Province is high, particularly among young people and those with low socioeconomic status. The study also identifies several factors that contribute to the spread of STDs, including lack of knowledge about STDs, lack of access to healthcare services, and risky sexual behavior. The study suggests that education and awareness programs, as well as access to healthcare services, are crucial in reducing the spread of STDs in the province. The study also recommends that policymakers and healthcare providers take into account the social and economic factors that contribute to the spread of STDs when developing policies and interventions to address this issue.Keywords: Sexually transmitted diseases; West Java province; Health services.